Development of a full‐length human protein production pipeline. (2nd June 2014) - Saul, Justin; Petritis, Brianne; Sau, Sujay; Rauf, Femina; Gaskin, Michael; Ober‐Reynolds, Benjamin; Mineyev, Irina; Magee, Mitch; Chaput, John; Qiu, Ji; LaBaer, Joshua
Abstract: There are many proteomic applications that require large collections of purified protein, but parallel production of large numbers of different proteins remains a very challenging task. To help meet the needs of the scientific community, we have developed a human protein production pipeline. Using high‐throughput (HT) methods, we transferred the genes of 31 full‐length proteins into three expression vectors, and expressed the collection as N‐terminal HaloTag fusion proteins in Escherichia coli and two commercial cell‐free (CF) systems, wheat germ extract (WGE) and HeLa cell extract (HCE). Expression was assessed by labeling the fusion proteins specifically and covalently with a fluorescent HaloTag ligand and detecting its fluorescence on a LabChip ® GX microfluidic capillary gel electrophoresis instrument. This automated, HT assay provided both qualitative and quantitative assessment of recombinant protein. E. coli was only capable of expressing 20% of the test collection in the supernatant fraction with ≥20 μg yields, whereas CF systems had ≥83% success rates. We purified expressed proteins using an automated HaloTag purification method. We purified 20, 33, and 42% of the test collection from E. coli, WGE, and HCE, respectively, with yields ≥1 μg and ≥90% purity. Based on these observations, we have developed a triage strategy for producing full‐length human proteins in these three expression systems.